Health-related quality of life among persons with initial mild, moderate, and severe or critical COVID-19 at 1 and 12 months after infection: a prospective cohort study - Anouk Verveen; Elke Wynberg; Hugo D. G. van Willigen; Udi Davidovich; Anja Lok; Eric P. Moll van Charante; Menno D. de Jong; Godelieve de Bree; Maria Prins; Hans Knoop; Pythia T. Nieuwkerk; the RECoVERED Study Group (BMC Medicine, 2022)
Abstract Background Currently, there is limited evidence about the long-term impact on physical, social and emotional functioning, i.e. health-related quality of life (HRQL) after mild or moderate COVID-19 not requiring hospitalization. We compared HRQL among persons with initial mild, moderate or severe/critical COVID-19 at 1 and 12 months following illness onset with Dutch population norms and investigated the impact of restrictive public health control measures on HRQL. Methods RECoVERED, a prospective cohort study in Amsterdam, the Netherlands, enrolled adult participants after confirmed SARS-CoV-2 diagnosis. HRQL was assessed with the Medical Outcomes Study Short Form 36-item health survey (SF-36). SF-36 scores were converted to standard scores based on an age- and sex-matched representative reference sample of the Dutch population. Differences in HRQL over time were compared among persons with initial mild, moderate or severe/critical COVID-19 using mixed linear models adjusted for potential confounders. Results By December 2021, 349 persons were enrolled of whom 269 completed at least one SF-36 form (77%). One month after illness onset, HRQL was significantly below population norms on all SF-36 domains except general health and bodily pain among persons with mild COVID-19. After 12 months, persons with mild COVID-19 had HRQL within population norms, whereas persons with moderate or severe/critical COVID-19 had HRQL below population norms on more than half of the SF-36 domains. Dutch-origin participants had significantly better HRQL than participants with a migration background. Participants with three or more COVID-19 high-risk comorbidities had worse HRQL than part participants with fewer comorbidities. Participants who completed the SF-36 when restrictive public health control measures applied reported less limitations in social and physical functioning and less impaired mental health than participants who completed the SF-36 when no restrictive measures applied. Conclusions Twelve months after illness onset, persons with initial mild COVID-19 had HRQL within population norms, whereas persons with initial moderate or severe/critical COVID-19 still had impaired HRQL. Having a migration background and a higher number of COVID-19 high-risk comorbidities were associated with worse HRQL. Interestingly, HRQL was less impaired during periods when restrictive public health control measures were in place compared to periods without.